Ensuring Good Administration through Development of Judicial Review in Sri Lanka: Special Reference to Fundamental Rights Based Jurisdiction as Grounds for Judicial Review - Udayanaganie, U.A.T. (University of Kelaniya, 2012)
Public authorities should exercise their powers within the four corners of the legislation. The grounds of judicial review are important in this context and up-to-date judicial review of administrative action has acquired many developments in its application. Though the doctrine of Ultra Vires was considered as ‘the central principle of administrative law’ it has moved from Ultra Vires rule to concern for the protection of individuals and for the control of power rather than powers or vires. Therefore the present tendency is to uphold the principles of good administration. On the other hand, the administrative law in Sri Lanka relating to judicial control has developed several principles such as proportionality, legitimate expectation, public trust doctrine and right to equality. In Sri Lanka, there are two ways of challenging the discretionary power of public authorities: writs and fundamental rights. In view of the fact that Sri Lanka has a fundamental rights system like India, the principles of good governance and public trust doctrine have been developed. However, these have nurtured the scope of exercising the power of judicial review of a given jurisdiction and accordingly have given finer meaning to the exercise of judicial power of the people by the judiciary and for upholding the rule of law. Therefore, this paper seeks to analyze the effectiveness of using fundamental rights based jurisdiction to challenge administrative action and how it ensures good administration. The main sources of the research are secondary resources such as library research and internet that include books, journal articles, cases and other related statutes. For the purpose of providing recommendations for Sri Lanka, a comparative study was done by the author in other jurisdictions including U.K., and India. According to the above facts, administrative law of Sri Lanka has moved towards a right based approach. However, many of the recently decided cases of Sri Lanka have shown the willingness of the superior courts to expand the scope of the control of administrative action to areas of fundamental rights. Under the fundamental rights jurisdiction and article 12(1), the judge can uphold the principle of rule of law via equality before the law. It is an essential feature of good and fair administration.